AI for digital warfare - Hageback, Niklas, author.
1 online resource
Keywords: AI for Digital Warfare explores how the weaponising of artificial intelligence can and will change how warfare is being conducted, and what impact it will have on the corporate world. With artificial intelligence tools becoming increasingly advanced, and in many cases more humanlike, their potential in psychological warfare is being recognised, which means digital warfare can move beyond just shutting down IT systems into more all-encompassing hybrid war strategies.